The Effects of Combined Low Frequency Repetitive Transcranial Magnetic Stimulation and Motor Imagery on Upper Extremity Motor Recovery Following Stroke - Pan, Wenxiu; Wang, Pu; Song, Xiaohui; Sun, Xiaopei; Xie, Qing (Frontiers in Neurology, 2019)
Objective: To investigate the effects of low frequency transcranial magnetic stimulation (LF-rTMS) combined with motor imagery (MI) on upper limb motor function during stroke rehabilitation. Background：Hemiplegic upper extremity activity obstacle is a common movement disorder after stroke. Compared with a single intervention, sequential protocol or combination of several techniques has been proven to be better for alleviate motor function disorder. Noninvasive neuromodulation techniques such as repetitive transcranial magnetic stimulation (rTMS) and motor imagery (MI) have been proved to augment the efficacy of rehabilitation. Methods: Participants were randomly assigned to 2 intervention cohorts: (1) experimental group (rTMS+MI group) was applied at 1Hz rTMS over the primary motor cortex of the contralesional hemisphere combined with audio-based MI; (2) control group (rTMS group) received the same therapeutic parameters of rTMS, and was applied audio-based non-specific MI in the meantime. LF-rTMS protocol was conducted in 10 sessions over 2 weeks for 30 min. Functional measurements include Wolf Motor Function Test (WMFT), the Fugl-Meyer Assessment Upper Extremity (UE-FMA) subscore, the Box and Block Test (BBT), and the Modified Barthel index (MBI) were conducted at baseline, end-intervention and 2 weeks postintervention. Results: All assessments of upper limb function improved in both groups at the end-intervention (week 2) and 2 weeks follow up (week 4). In particular, significant differences were observed between two groups at end-intervention and after intervention (P＜0.05). In these findings, we saw greater changes of WMFT (p<0.01), UE-FMA (p<0.01), BBT (p<0.01), and MBI (p<0.001) scores in the experimental group. Conclusions: LF-rTMS combined with MI had a positive effect on motor function of upper limb and can be used for the rehabilitation of upper extremity motor recovery in stroke patients.